2007
DOI: 10.1002/ijc.23053
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated expression of TIMP‐1 and TIMP‐2 in bone inhibits osteolytic degradation by human prostate cancer

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes that play critical roles in the pathogenesis of human cancers. Clinical trials using synthetic small molecule MMP inhibitors have been carried out but with little success. Tissue inhibitors of metallopro-teinases (TIMPs) are endogenous inhibitors that block the extrac-ellular matrix-degrading activity of MMPs. Here, we investigated the possibilities of genetically modifying human bones with TIMPs to create a high-TIMP bone microenvironment, which is host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Importantly, TIMP1 up-regulation in PTC was reported recently [34]. Earlier studies indicated that TIMP1 displayed anti-cancer activities [35,36], however, recent studies demonstrated a paradoxical protumor effect of TIMP1 [31,37]. In the present study, TIMP1 was up-regulated in PTC and ATC, while down-regulated in FTC, which was in accordance with the findings above.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, TIMP1 up-regulation in PTC was reported recently [34]. Earlier studies indicated that TIMP1 displayed anti-cancer activities [35,36], however, recent studies demonstrated a paradoxical protumor effect of TIMP1 [31,37]. In the present study, TIMP1 was up-regulated in PTC and ATC, while down-regulated in FTC, which was in accordance with the findings above.…”
Section: Discussionsupporting
confidence: 92%
“…TIMPs balance the activity of proteases in cooperation with additional factors within the tumor microenvironment but may also promote tumor metastases (36). Another study reports that decreasing the expression of TIMPs by gene transfer or by chemical agents results in decreased tumor metastases (37). Repression of several other genes, such as BMP-2, BMP-6, IL-8, and TGF-β, by SKI-606 is most likely beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Most of them use recombinant adenoviruses or lentiviruses, 39,40 but because of the possibility of recombination with wildtype adenovirus and the antiviral immune response, these approaches have been limited to research use. 41 More recently, electroporation has been applied in vivo and shown to be potentially safe for clinical use.…”
Section: Discussionmentioning
confidence: 99%